2012
DOI: 10.1590/s1677-55382012000200015
|View full text |Cite
|
Sign up to set email alerts
|

Primary fixation of mini slings: a comparative biomechanical study in vivo

Abstract: ARTICLE INFO _______________________________________________________________ _____________________

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
(14 reference statements)
1
16
0
Order By: Relevance
“…New generation of single incision mid-urethral slings were introduced from last decade with the intent to cure stress urinary incontinence in an outpatient with short operation time, less pain and less bleeding (Palma et al, 2010(Palma et al, , 2012(Palma et al, , 2013Pushkar et al, 2010;Enzelsberger et al, 2011;Smith et al, 2011). Several clinical studies are ongoing to investigate the safety and efficacy of these new minimally invasive procedures compared to the gold standard surgeries, the Burch colposuspension and the pubovaginal slings with established high cure rates in the treatment of SUI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…New generation of single incision mid-urethral slings were introduced from last decade with the intent to cure stress urinary incontinence in an outpatient with short operation time, less pain and less bleeding (Palma et al, 2010(Palma et al, , 2012(Palma et al, , 2013Pushkar et al, 2010;Enzelsberger et al, 2011;Smith et al, 2011). Several clinical studies are ongoing to investigate the safety and efficacy of these new minimally invasive procedures compared to the gold standard surgeries, the Burch colposuspension and the pubovaginal slings with established high cure rates in the treatment of SUI.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies are ongoing to investigate the safety and efficacy of these new minimally invasive procedures compared to the gold standard surgeries, the Burch colposuspension and the pubovaginal slings with established high cure rates in the treatment of SUI. Despite high success rates with rectus facia pubovaginal sling even in complicated cases of SUI, there are some complications reported with this approach, such as wound infections, de novo urge incontinence and obstructive symptoms (Shumaker et al, 1994;Bump et al, 1996;Abrams et al, 2002;Athanasopoulos et al, 2011;Enzelsberger et al, 2011;Palma et al, 2012;Sivaslioglu et al, 2012). Ophira mini sling is among the new innovative systems, proposed to overcome these drawbacks, omit graft harvest and reduce excessive tension on bladder neck (Cody et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study that compared primary fixation of five different mini slings and one polyproylene mesh showed that the Ophira TM mini sling system presented the best fixation in Wister rats (Palma et al, 2012). However, it is important that we must critically evaluate these technologies in daily practice.…”
Section: Introductionmentioning
confidence: 99%